Who do we follow online? An experimental study on source clarity and social proximity in digital health communication - Li, Junhui; Shi, Chunsheng (Frontiers in Public Health, 2025)
Public health communication increasingly relies on digital channels where advice is encountered from diverse sources that vary in source clarity (whether the sender is perceived as clearly identifiable) and social proximity (whether the sender is perceived as relationally close). To examine how these sources shape compliance with health advice, we conducted a randomized controlled online experiment (N = 810) simulating a social media environment in which each participant viewed one weight-management post attributed to one of eight sources: parents, friends, colleagues, doctors, health influencers, news agencies, Wikipedia, or AI chatbots. We measured intended compliance and four cognitive responses: perceived credibility, psychological reactance, attention, and comprehension. Messages from single specified sources (parents, friends, colleagues, doctors, influencers, news agencies) increased intended compliance by 13–17 percentage points compared with composite diffuse sources (AI chatbots, Wikipedia). Within specified senders, significant others (parents, friends, colleagues) outperformed professional experts (doctors, influencers, news agencies) by 11–16 points. Mediation analyses showed that source clarity operated primarily through enhanced credibility, while social proximity operated through higher credibility and lower reactance; attention and comprehension did not mediate these effects. Subgroup analyses indicated stronger effects among participants with chronic conditions, higher health literacy, or behaviorally aligned daily routines. These findings suggest that, in a networked digital environment, compliance with health advice is influenced less by professional authority or aggregated information, and more by identifiable and socially close sources. The study provides evidence-based guidance for selecting sources and designing messages in public health promotion.